Corpo lavrado: a poesia telúrica de Ana Paula Tavares - Fernandes, Maria Lúcia Outeiro [UNESP]; Silva, Paulo César Andrade da [UNESP] (My University, 2011)
In this paper we analyze how the symbols of land and woman are articulated in the lyric from Ana Paula Tavares. Such motifs, applicants at O lago da lua (1999), will take on a structuring in the poetic universe from this Angolan writer, because architect his being in the world at an existential level and political. Paula Tavares gives her voice to express, with defiance and tenderness, the bitter cry of women prisoners in their own silence. The symbiosis between land and woman works as formative and empowering element of identity

Neste trabalho analisaremos de que modo a simbologia da terra e da mulher se articulam na lírica da poetisa Ana Paula Tavares. Tais motivos, recorrentes em O lago da lua (1999), ganham dimensão estruturadora no universo poético da escritora angolana, pois arquitetam o seu estar no mundo no plano existencial e político. Paula Tavares cede a sua voz para expressar, com rebeldia e ternura, o clamor amargo das mulheres encarceradas no seu próprio silêncio. A simbiose entre terra e mulher funciona como elemento formador e fortalecedor da identidade.
Keywords: Ana Paula Tavares; Angolan poetry; Land; Woman; Memory; Ana Paula Tavares; Poesia angolana contemporânea; Terra; Memória; Mulher